Painful regret and elation at the track - Adi Schnytzer; Barbara Luppi (Bar-Ilan University, Department of Economics, 2008)
We present an empirical study of loss aversion in the Hong Kong horse betting market. We provide evidence of the presence of loss aversion in a context of complete absence of the favourite-longshot bias. This would suggest that, since loss aversion is a psychological bias, the favourite-longshot bias may not necessarily be caused by psychological issues and may be due, for instance, to informational asymmetry. We investigate different types of bettors and their attitude towards loss aversion. Our data set enables us to distinguish approximately among insiders, unsophisticated outsiders and sophisticated outsiders. The results show clearly that even sophisticated bettors are beset by loss aversion, while even unsophisticated outsiders display no favourite-longshot bias. Thus, our paper provides evidence that loss aversion may be an attitude innate rather than learned, regardless of the level of sophistication in designing economic behaviour or the extent of information asymmetry. Chen et al (2006) show that capuchin monkeys display biases when faced with gambles, including loss aversion, and provide evidence that loss aversion extends beyond humans. The present work supports the idea that loss aversion may be a more universal bias, arising regardless of experience and culture and demonstrates that loss aversion is displayed even by those bettors regarded in the market as 'smart money'. Further, we find that more sophisticated and experienced bettors display a higher level of loss aversion. This result is consistent with the findings of Haigh and List (2005), who show that professional traders in financial markets exhibit more loss aversion than do students.
Keywords: 330; Pferdesport; Glücksspiel; Risikopräferenz; Entscheidung bei Risiko; Hongkong